¿Tienen los empleadores el deber de seguir abonando salarios, a pesar de no recibir trabajo a cambio? Razones para su debida consideración - Aguinaga Meza, Ernesto Alonso (2024)
This paper, drawing from what occurred before and after the pandemic, is a substantiation endeavour aimed at determining the grounds that authorize the imposition, by law, of the corporate duty to continue paying wages, despite not receiving -or even expecting- work in return. To this end, first, it shows that the law in force already provides a powerful legal reason to justify legislative interventions in this sense: the constitutionalized social dimension of wages. Subsequently, in order to support the constitutional principle in question, it argues that there are sufficient moral reasons to implement distributive mechanisms of business income that even cover cases in which it is factually impossible to offer work in exchange. Finally, appealing to the notion of “special positive duty”, it asserts that the aforementioned constitutional provision is the materialization in the labour sphere of the ethical duty of every person to provide assistance to others who are in a hazardous situation or need, provided that doing so involves a trivial effort or sacrifice.